Cytotoxicity Assay of Agaricus Bisporus Extract , Oxaliplatin and Combination of both on Melanoma-B16 and Vero-101 Cell line:An in Vitro study - Suhad Mohammed, (University of Thi-Qar Journal of Science, 2020)
The present study included extracted Agaricus bispours and estimated proteins and carbohydrates amount in extract then assessment activity of methanolic crude extract of medicinal mushroom A. bisporus as in vitro anticancer by using melanoma-B16 cell line ,and compared with chemotherapy Oxaliplatin and approved reduction toxic effect of chemotherapy on normal cells when exposed to combination between chemotherapy and mushroom extract on normal vero-101 cell line. Proteins and carbohydrate estimation results referred to there are about 219.33 and 412.98 µg/ml respectively. The results showed that inhibition rate of melanoma-B16 cell line was about 82.15% according to cytotoxicity assay test by crystal violate when treated these cells by methanol crude extract of A. bisporus at 1000 mg/ml .But the cytotoxicity assay of using chemotherapy oxaliplatin on melanoma-B16 at 100 mg/ml results appeared that the inhibition rate was 64.52%. The cytotoxicity assay of combination between methanolic crude extract of A.bisporus 1000 mg/ml and oxaliplatin 100 mg/ml results the inhibition rate was 70.04% on melanoma B-16 cell line.Crystal violate cytotoxicity assay of treatments on normal vero-101 cell line results were revealed that non significantly inhibition of A.bisporus extract on normal cells only 5.37%.While chemotherapy oxaliplatin have inhibition rate on vero-101 normal cell line about 65% ,While the combination treatment cytotoxicity assay on vero-101 normal cell line showed that inhibition rate was reduced to 20.35% comparing with cancer cell which was about 65.3%